Nucleosome movement by CHRAC and ISWI without disruption or trans-displacement of the histone octamer. - Langst, G.; Bonte, E.J.; Corona, D.F.; Becker, P.B. (Cell, 1999)
The chromatin accessibility complex (CHRAC) belongs to the class of nucleosome remodeling factors that increase the accessibility of nucleosomal DNA in an ATP-dependent manner. We found that CHRAC induces movements of intact histone octamers to neighboring DNA segments without facilitating their displacement to competing DNA or histone chaperones in trans. CHRAC-induced energy-dependent nucleosome sliding may, in principle, explain nucleosome remodeling, nucleosome positioning, and nucleosome spacing reactions known to be catalyzed by CHRAC. The catalytic core of CHRAC, the ATPase ISWI, also mobilized nucleosomes at the expense of energy. However, the directionality of the CHRAC- and ISWI-induced nucleosome movements differed drastically, indicating that the geometry of the native complex modulates the activity of its catalytic core.